‘English-only’ English medium instruction: Mixed views in Thai and Vietnamese higher education - Sahan, Kari; Galloway, Nicola; McKinley, Jim (Language teaching research : LTR, 2025)
Emerging from the growing body of work on English medium instruction (EMI) in higher education are challenges to policy implementation, particularly when it is implemented top-down without a careful needs analysis or when it fails to address problems associated with ‘English-only’ implementation and so-called ‘native speaker’ norms. Our study responds to this need by exploring the role of English in EMI classrooms. We draw on data collected from 17 universities in Thailand and Vietnam using questionnaires with 1,377 students, 83 teachers of English for academic purposes (EAP), and 148 content teachers, as well as interviews with 35 students, 31 EAP teachers, and 28 content teachers. We also draw on data from 14 focus groups with teachers and students at seven universities in Vietnam. Findings reveal differences in attitudes amongst stakeholders and highlight that the L1 in EMI classrooms in Thailand and Vietnam, albeit used sparingly, is a useful pedagogical tool. Overall, however, participants preferred native-accented teachers with experience abroad, and English-only instruction. This study calls for more research into raising awareness of Global Englishes and translanguaging practices to challenge such attitudes, university language policies, and teacher recruitment practices that seem to reflect native-speakerism and discourage bilingual instruction or L1 use in EMI classes.